Spontaneous luminal disequilibrium pH in S3 proximal tubules. Role in ammonia and bicarbonate transport. - Kurtz, I (1986)
We determined whether a spontaneous luminal disequilibrium pH, pHdq (pH measured - pH equilibrium), was present in isolated perfused rabbit S2 and S3 proximal tubules. Luminal pH was measured by perfusing with the fluorescent pH probe 1,4-DHPN, and the equilibrium pH was calculated from the measured collected total CO2 and dissolved CO2 concentrations. S2 tubules failed to generate a spontaneous pHdq. S3 tubules generated a spontaneous acidic pHdq of -0.46 +/- 0.15 (P less than 0.05), which was obliterated following the addition of carbonic anhydrase (0.1 mg/ml) to the perfusate. In S3 tubules perfused and bathed in 4 mM total ammonia, luminal total ammonia rose from 4.08 +/- 0.05 mM (perfusate) to 4.95 +/- 0.20 mM (collected fluid) (P less than 0.02). Carbonic anhydrase added to the perfusate prevented the rise in the collected total ammonia concentration. We conclude that the rabbit S3 proximal tubule lacks functional luminal carbonic anhydrase. The acidic pHdq in the S3 segment enhances the diffusion of NH3 into the lumen. In contrast, the S2 segment has functional luminal carbonic anhydrase.